The Reflection of Cultural Identity of Gayo Society, Central Aceh Regency in Tawar Sedenge Song - Dini, Tria Ayu; Utomo, Udi; Triyanto, Triyanto (Catharsis, 2018)
Tawar Sedenge is a song from Gayo, Aceh province. For Gayo society, this song has an important existence till present. It is marked by the sung of Tawar Sedenge song in Takengon’s formal events and every national ceremony as a distraction of Indonesia Raya song. Tawar Sedenge song has an important role in Gayo society because this song’s lyrics contains a spirit of nationalism that awaken the spirit of Gayo society to achieve the progress and weathliness. This research aims at analyzing and understanding the reflection of Gayo’s cultural identity in Tawar Sedenge song. The research method was qualitative. The research location was Takengon, Central Aceh Regency. The techniques of data collection were observation, interview, and document study. The technique of data validity used source triangulation. Analysis data technique used analysis desciptive. The research result shows that lyrics and music elements contained in this song prove that this song is reflected Gayo’s cultural identity that is from the cultural identity elements based on belief, language, and behavior. First, the element of belief exists in the third stanza lyrics. Secondly, the language element used is Gayo’s language, the behavior is seen from the costume worn by the conductor,i.e., Kerawang Gayo, Gayo’s raditional costume.. The behavior can also be seen from the solemn posture in singing the song. Therefore, it is believed that the elements of Tawar Sedenge song is the reflection of Gayo culture.